Developing and Psychometric Assessment of Dichotic Nonsense Syllable Test in Persian Speaking Normal Adults - Abdollah Moosavi; Asma Khadiv; Ahmad Reza Nazeri; Enayatollah Bakhshi; Behrooz MahmoodiBakhtiari; Nasrin Qhanbari (Vesnu Publications, 2015)
Introduction: Dichotic speech recognition includes simultaneously presentation of competing stimuli to both ears and has been used to investigate the hemispheric dominance for language and auditory processing abilities in adults and children. The present study aimed to develop the Persian version of dichotic nonsense syllable test and determination of its psychometrics properties. Materials and Methods: This instrumental, non-experimental study with a methodological pattern consists of three main parts: developing Persian version of dichotic nonsense syllable test, evaluation of  its content validity by use of Content Validity Ratio, running it on 80 (40 males and 40 females) normal adults aged 18-25 years (mean age: 21.16 ± 2.28 Years), which is likely to be selected according to the inclusion criteria from students from universities located at Tehran, Iran to determine the tests reliability. Results: The Content Validity Ratio for each items of the test was more than 0.62. The amount of Cronbach's alpha coefficient and intra class correlation (ICC) was, 0.86 and 0.75, respectively. Test- retest correlation found out to be 0.83 after 2 to 4 weeks intervals. Conclusion: Results show this Persian version of dichotic nonsense syllable test possesses acceptable content validity and reliability and can be used in clinical trials and research.